DESKRIPSI PERBEDAAN FONOLOGI BAHASA -BAHASA DI WILAYAH BARAT PROVINSI JAWA TENGAH - Junawaroh, Siti (Faculty of Humanities, Diponegoro University, 2016)
Study description phonology differences in the western region of Central Java Province include Javanese and Sundanese used side by side in the region of Brebes and Cilacap . In the study dialectology , phonology deskription serves to illustrate the differences and variations correspondence contained in the observation point. For the western region of Central Java province contained the correspondence was perfect and less than perfect correspondence . Perfect correspondence in the form of correspondence sound b- w . Correspondence less than perfect form of correspondence h- Ø , In addition , there are also variations consonants d-n, h-k , h-ng , h-s , g-k , w-c , K- Ø and vocal variety , i-e , u-o , u-a ,VV - V ,V - Ø.